Curcumin ameliorates atrophy of seminal vesicle via reduction of oxidative stress in castrated mice - Rui Li; Hao Li; Ke Rao; Kang Liu; Yan Zhang; Xiaming Liu; Tao Wang; Shaogang Wang; Zhuo Liu; Jihong Liu (PeerJ, 2019)
Background The growth and function of seminal vesicle are dependent on androgen. This study was conducted to investigate the role of oxidative stress in castration-induced seminal vesicle atrophy and to explore the effects of curcumin, an antioxidant extracted from rhizome of turmeric, on seminal vesicle of castrated mice. Methods C57BL/6J mice were randomly divided into three groups: control, castration, and castration with curcumin (n = 10 for each group). After surgical castration, mice in the curcumin treatment group received intragastric administration of curcumin at 100 mg/kg body weight for 4 weeks, whereas mice in the other two groups were treated with olive oil. After that, the body weight, seminal vesicle weight and serum testosterone of mice were measured. Apoptosis and oxidative stress levels in seminal vesicle were also determined. Results After castration, both the weight and size of seminal vesicle decreased dramatically. The expression of three NADPH oxidase (NOX) subtypes: NOX1, NOX2 and NOX4, increased in seminal vesicle of castrated mice, resulting in high level oxidative stress. The ratio of Bax to Bcl-2 was also elevated after castration, accompanied by enhanced caspase3 activity. Additionally, castration increased the number of apoptotic cells in seminal vesicle. Curcumin treatment could inhibit the expression of NOX1, NOX2 and NOX4, decreasing oxidative stress and apoptosis. The atrophy of seminal vesicle caused by castration was ameliorated by curcumin. Conclusion Castration could cause atrophy of seminal vesicle probably via inducing oxidative stress. Curcumin treatment could reduce the oxidative stress in seminal vesicle by decreasing the expression of NOX1, NOX2 and NOX4, thereby ameliorating apoptosis and atrophy of seminal vesicle. Oxidative stress might play a role in castration-induced seminal vesicle atrophy.